Sensory methodologies used in descriptive studies with consumers: Check-All-That-Apply (CATA) and variations (Research, Society and Development, 2020)
Food presents sensory attributes that can be identified, described and quantified using descriptive sensory methods. These methods have been used to developing of new products, quality control, formulation changes and to the evaluation of shelf life in the food industry. Traditional descriptive techniques have as limitations the requirement of trained evaluators since they present high degree of difficulty/complexity of these evaluations. Another disadvantage is the time needed to conduct the training, making the method very expensive. To reduce the time analysis and costs of traditional descriptive techniques, recent research is seeking to develop and validate methodologies that make possible to describe foods through the use of consumers, avoiding the need of trained judges. The objective was to describe the advances of the descriptive methodology named Check-All-That-Apply (CATA) and their variations, as well as their advantages and limitations.